Physically Sufficient Neural Mechanisms of Consciousness - Owen, Matthew; Guta, Mihretu P. (Frontiers in Systems Neuroscience, 2019)
Neural correlates of consciousness (for brevity NCC) are foundational to the scientific study of consciousness. David Chalmers (2000) has provided the most informative and influential definition of NCC, according to which neural correlates are minimally sufficient for consciousness. However, the sense of sufficiency needs further clarification since there are several relevant senses with different entailments. In section one of this article, we give an overview of the desiderata for a good definition of NCC and Chalmers’s definition. The second section analyzes the merit of understanding the sufficiency of neural correlates for corresponding consciousness according to three relevant types of sufficiency: logical, metaphysical, and physical. In section three, a theoretical approach to consciousness studies is suggested in light of the sense in which NCC are sufficient for consciousness. Section four addresses a concern some might have about this approach. By the end, it will become apparent that our conception of NCC has important implications for research methodology, neuroethics, and the vitality of the search for NCC.